Land Use Planning for Natural Hazards - Bathrellos, George D.; Skilodimou, Hariklia D. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Natural hazard events are able to significantly affect the natural and artificial environment. In this context, changes in landforms due to natural disasters have the potential to affect and, in some cases, even restrict human interaction with the ecosystem. In order to minimize fatalities and reduce the economic impact that accompanies their occurrence, proper planning is crucial. Land use planning can play an important role in reducing current and future risks related to natural hazards. Land use changes can lead to natural hazards and vice versa: natural hazards affect land uses. Therefore, planners may take into account areas that are susceptible to natural hazards when selecting favorable locations for land use development. Appropriate land use planning can lead to the determination of safe and non-safe areas for urban activities. This Special Issue focuses on land use planning for natural hazards. In this context, various types of natural hazards, such as land degradation and desertification, coastal hazard, floods, and landslides, as well as their interactions with human activities, are presented.